PENYULUHAN KONSERVASI EKOWISATA HUTAN MANGROVE TAPAK MELALUI PENANAMAN MANGROVE DI DESA TUGUREJO KOTA SEMARANG - Yuliyani, Dwi Nur; Sari, Siti Nurindah; -, Kasanah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
under order to keep coastal ecosystems under check, mangrove forests are crucial. The mangrove woods of Tugu Village, Tugurejo District, Semarang City, are a major draw for ecotourists. The research questions that this study seeks to address are as follows: (1) Which mangrove species would be most suited for planting in the Tapak mangrove forest tourist preservation area in Tugu Village, Tugurejo District, Semarang City? (2) When planting mangrove seedlings, what methods are used in this region? This research documents the successful process of planting mangrove seedlings and employs a qualitative approach to identify potential mangrove kinds using observation, interviews, and literature analysis. Sustainable ecotourism management and conservation initiatives in Tugurejo Village's mangroves are two areas that can benefit from this study's findings. Keywords: Mangrove, Ecotourism, Counselling, Conservation